Pesantren Culture in Building Generations and Nations - Rahayu, Puji; Baqi Ghrafiza, Ahmad (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
Pesantren culture is formed as a result of the dialectic between the faith that is believed and the cultural reality that develops in the Pesantren community. This is because the Pesantren community believes that the culture contains high moral values ​​and is beneficial for life, maintaining harmony with society and the surrounding environment. Culture can be interpreted in 3 parts, namely intellectual, spiritual and aesthetic development, which leads to visible culture and invisible culture. Among the cultures of modern Pesantren is developing the values ​​of aqidah, sharia, devotion, intellectualism, leadership, discipline, independence, simplicity, cooperation, responsibility, and mastery of foreign languages, both Arabic and English, in accordance with the demands of the times.